Key transportation indicators summary of a workshop - Casey, Jamie; Norwood, Janet Lippe (Compass series (Washington, D.C.), 2002)
"The purpose of the Worksshop on Transportation Indicators was to discuss issues relating to transportation indicators and provide the Bureau of Transportation Statistics with new ideas for issues to address."--P. 1.